Quantitative proteomics reveals the protective effects of Yinchenzhufu decoction against cholestatic liver fibrosis in mice by inhibiting the PDGFRβ/PI3K/AKT pathway - Meng, Qian; Zhu, Hongwen; Li, Yuanyuan; Peng, Xiaotian; Wang, Tianming; Huang, Hui; Zhou, Hu; Liu, Yuejia; Ru, Sujie; Wu, Jiasheng; Ma, Yueming (Frontiers in Pharmacology, 2024)
Yinchenzhufu decoction (YCZFD) is a traditional Chinese medicine formula with hepatoprotective effects. In this study, the protective effects of YCZFD against cholestatic liver fibrosis (CLF) and its underlying mechanisms were evaluated in a mouse model of 3,5-diethoxycarbonyl-1,4-dihydro-collidine (DDC)-induced cholestasis. YCZFD significantly decreased the levels of serum biochemical, liver injury, and fibrosis indicators. Data-independent acquisition-based mass spectrometry was performed to investigate proteomic changes in the livers of mice in three groups: control, model, and model treated with high-dose YCZFD. In total, 460 differentially expressed proteins (DEPs) were identified. Enrichment analyses of these DEPs revealed that YCZFD influenced multiple pathways, including PI3K-Akt, focal adhesion, ECM–receptor interaction, glutathione metabolism, and steroid biosynthesis pathways. The expression of platelet derived growth factor receptor beta (PDGFRβ), a receptor associated with the PI3K/AKT and focal adhesion pathways, was upregulated in the livers of cholestatic mice but downregulated by YCZFD. The effects of YCZFD on the expression of key proteins in the PDGFRβ/PI3K/AKT pathway were further confirmed in mice and transforming growth factor-β-induced hepatic stellate cells. We uncovered seven active ingredients (chlorogenic acid, scoparone, isoliquiritigenin, glycyrrhetinic acid, formononetin, atractylenolide I, and benzoylaconitine) of YCZFD that may regulate PDGFRβ expression. Overall, YCZFD substantially protects against DDC-induced CLF mainly through regulating the PDGFRβ/PI3K/AKT signaling pathway.